Hydrosonographic assessment of the effects of 2 different suturing techniques on healing of the uterine scar after cesarean delivery1. Issue 3 (28th February 2014) - Sevket, Osman; Ates, Seda; Molla, Taner; Ozkal, Fulya; Uysal, Omer; Dansuk, Ramazan
Abstract: Objective: To compare the effects of 2 suturing techniques (single versus double layer) on healing of the uterine scar after a cesarean delivery. Methods: In the present randomized, prospective study, 36 women with a term pregnancy who had an elective cesarean delivery were randomly assigned to closure of the uterine incision with a single‐layer locked suture or with a double‐layer locked/unlocked suture. Six months after the operation, the integrity of the cesarean scar at the uterine incision site was assessed by hydrosonography. The healing ratio and the thickness of the residual myometrium covering the defect were calculated as markers of uterine scar healing. Results: There were no significant differences between the groups in terms of estimated blood loss, operation time, or additional hemostatic suture. However, the mean thickness of the residual myometrium covering the defect was 9.95 ± 1.94 mm after a double‐layer closure and 7.53 ± 2.54 mm after a single‐layer closure ( P = 0.005). The mean healing ratio was significantly higher after a double‐layer closure (0.83 ± 0.10) than after a single‐layer closure (0.67 ± 0.15; P = 0.004). Conclusion: A double‐layer locked/unlocked closure of the uterine incision at cesarean delivery decreases the risk of poor uterine scar healing.